Identification of the Germline Mutation Profile in Esophageal Squamous Cell Carcinoma by Whole Exome Sequencing - Deng, Jiaying; Weng, Xiaoling; Ye, Junyi; Zhou, Daizhan; Liu, Yun; Zhao, Kuaile (Frontiers in Genetics, 2019)
Background: Esophageal squamous cell carcinoma (ESCC) is associated with poor prognosis and occurs with high frequency in China. The germline mutation profile in ESCC remains unclear, and therefore, the discovery of oncogenic alterations in ESCC is urgently needed. This study investigates the germline mutation profile and reveals associations among genotype-environment interactions in ESCC. Methods: Whole exome sequencing and follow-up analysis were performed in 77 matched tumor-normal ESCC specimens to examine the germline profiles. Additionally, associations among genotype-environment interactions were investigated. Results: We identified 84 pathogenic/likely pathogenic mutations and 51 rare variants of uncertain significance (VUS). Twenty VUS with InterVar evidence of a score of moderate pathogenicity (PM) 2/PM2+ supporting pathogenicity (PP) 1 were found to have pathogenic significance. CYP21A2 was the most frequently mutated gene, and the p.Gln319* variant was identified in 6.5% (5/77) of patients. The TP53 p.V197E mutation, located within the DNA binding domain, was found in 1.3% (1/77) of patients. In total, the 11.7% (9/77) of individuals with homologous recombination (HR) VUS were more likely to have well-differentiated tumors than those without (P = 0.003). The degree of lymph node metastasis was correlated with homologous recombination deficiency (HRD) and VUS group (P<0.05). Moreover, the 10.4% (8/77) of individuals with mismatch repair (MMR) VUS had a higher tumor mutational burden (TMB), although the correlation was not significant. Conclusions: Our study identified the germline mutation profiles in ESCC, providing novel insights into the molecular pathogenesis of this disease. Our results may also serve as a useful resource for the exploration of the underlying mechanism of ESCC and may provide information for the prevention, diagnosis and risk management of ESCC.